App-based food Go/No-Go training: User engagement and dietary intake in an opportunistic observational study. (1st October 2021) - Aulbach, Matthias Burkard; Knittle, Keegan; van Beurden, Samantha Barbara; Haukkala, Ari; Lawrence, Natalia S.
Abstract: Food Go/No-Go training aims to alter implicit food biases by creating associations between perceiving unhealthy foods and withholding a dominant response. Asking participants to repeatedly inhibit an impulse to approach unhealthy foods can decrease unhealthy food intake in laboratory settings. Less is known about how people engage with app-based Go/No-Go training in real-world settings and how this might relate to dietary outcomes. This pragmatic observational study investigated associations between the number of completed app-based food Go/No-Go training trials and changes in food intake (Food Frequency Questionnaire; FFQ) for different healthy and unhealthy food categories from baseline to one-month follow-up. In total, 1234 participants ( m (BMI)  = 29 kg/m 2, m (age)  = 43years, 69% female) downloaded the FoodT app and completed food-Go/No-Go training at their own discretion (mean number of completed sessions = 10.7, sd  = 10.3, range: 1–122). In pre-registered analyses, random-intercept linear models predicting intake of different foods, and controlled for baseline consumption, BMI, age, sex, smoking, metabolic syndrome, and dieting status, revealed small, significant associations between the number of completed training trials and reductions in unhealthy food intake ( b = -0.0005, CI 95 = [-0.0007;-0.0003]) and increases in healthy food intake ( b = 0.0003, CI 95  = [0.0000; 0.0006]). These relationships varied by food category, and exploratory analyses suggest that more temporally spaced training was associated with greater changes in dietary intake. Taken together, these results imply a positive association between the amount of training completed and beneficial changes in food intake. However, the results of this pragmatic study should be interpreted cautiously, as self-selection biases, motivation and other engagement-related factors that could underlie these associations were not accounted for. Experimental research is needed to rule out these possible confounds and establish causal dose-response relationships between patterns of engagement with food Go/No-Go training and changes in dietary intake.